Analisis Pengelolaan Aset Tetap Studi Kasus DPRD Sumut - Fajri Mustofa Akbar; Yenni Samri Juliaty Nasution (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2022)
Fixed assets or assets are all goods purchased and obtained at the expense of the State Revenue and Expenditure Budget (APBN) or from other legitimate acquisitions, both current and non-current and their parts. This research is aimed at reviewing the fixed asset management system based on PSAK No. 7 regarding fixed assets. The purpose of this study was to determine the suitability of fixed asset management at the North Sumatra DPRD Office with PSAP No. 7. This research also uses a qualitative approach, information collection techniques are carried out by interviews and documentation. From the results of research conducted on the management of fixed assets at the North Sumatra DPRD Office, especially the field of accounting regarding recognition, measurement, disclosure is in accordance with Statement of Government Accounting Standards Number 7.